2022
DOI: 10.3390/su14095736
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Street Functionality and Restorative Benefit: Developing an Expectation–Current Approach to Street Design

Abstract: The importance of creating a better living environment that is conducive to public health has become increasingly prominent in the post-epidemic era. The restorative potential of urban streets has been emphasized recently, as these spaces of our everyday lives may provide people with restorative experiences. However, there is still no efficient way of delivering restorative street design, because no specific standard has been set to indicate the form such streets should take. A street has limited spaces but mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Rooted in the Perceptual Restorative Scale (PRS), a widely employed tool for gauging environmental revitalization benefits, RCS presents a more pertinent measurement structure aligned with the four environmental dimensions delineated by ART: being away, extent, fascination, and compatibility 33 . Previous inquiries have substantiated its efficacy in exploring anticipations and prevailing levels of street recovery 34 . As delineated in Table 3 , RCS encompassed 15 items, with participants assigning ratings on a seven-point Likert scale, ranging from -3 (no perception) to 3 (strong perception).…”
Section: Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rooted in the Perceptual Restorative Scale (PRS), a widely employed tool for gauging environmental revitalization benefits, RCS presents a more pertinent measurement structure aligned with the four environmental dimensions delineated by ART: being away, extent, fascination, and compatibility 33 . Previous inquiries have substantiated its efficacy in exploring anticipations and prevailing levels of street recovery 34 . As delineated in Table 3 , RCS encompassed 15 items, with participants assigning ratings on a seven-point Likert scale, ranging from -3 (no perception) to 3 (strong perception).…”
Section: Environmentsmentioning
confidence: 99%
“…The combination of subjective evaluations and physiological indices is a standard methodology for assessing stress recovery 30 , 31 . Building upon the Attention Recovery Theory (ART) developed by Rachel and Stephen 32 , the Restorative Components Scale (RCS) evaluates stress recovery through four dimensions: being away, extent, fascination, and compatibility, with its effectiveness demonstrated by Laumann et al and Yin et al 33 , 34 . Physiologically, stress recovery correlates significantly with cardiovascular system activity, with blood pressure (BP) and heart rate variability (HRV) serving as reliable indicators.…”
Section: Introductionmentioning
confidence: 99%
“…After referring to similar studies [54,55] that were conducted within a Chinese context, a revised version of the RCS [53] that is more conveyable in Chinese was employed to investigate participants' perceptions of restorations in the ten selected pocket parks. The RCS contains 15 items (Table 2); three of them describe the being away (B) component, three of them describe the extent (E) component, five of them describe the fascination (F) component and four of them describe the compatibility (C) component proposed in the ART [11,[34][35][36].…”
Section: Rcs To Measure Pocket Park Restorativenessmentioning
confidence: 99%
“…Moreover, people can obtain psychological restoration in street settings. The visibility of streetscape greenery has proven to be most relevant to people's perceived restorativeness [51]. Relevant indicators also include pavements, the presence of other people, coloured flowers, streetside buildings, and cars [52].…”
Section: Urban Streetscape and Environmental Equitymentioning
confidence: 99%
“…On the contrary, in another study exploring the justice of streetscape visual compensation, streetscapes with positive compensation effects on relieving road anger were mainly gathered around People's Square and Yuyuan Gardem where less health-promotive streets were found [66]. The observed positive benefits of urban streetscapes proved their importance in improving environmental quality and people's perceptions [51][52][53]. Relevant research findings also confirmed their role as an essential landscape resource and, thus, the equity that is a key aspect in the pursuit of environmental justice.…”
Section: The Health Equity Promoted By Urban Streetscapementioning
confidence: 99%